The future of cities. Opportunities, challanges and the way forward. - (:unkn) unknown (My University, 2019)
This report identifies challenges influencing the future of cities in Europe and beyond. It also presents several perspectives from which to look at resolving these issues.
Keywords: Stadtforschung; Zukunftsentwicklung; Urbanismus; Urbanisierung; Trend; Wohnungswesen; Mobilität; Kommunale Dienstleistung; Alterung; Gesundheit; Segregation; Kommunaler Umweltschutz; Kommunaler Klimaschutz; Öffentlicher Raum; Innovation; Technische Infrastruktur; Urban Governance; Glossar